2014
DOI: 10.1136/bmj.f7412
|View full text |Cite
|
Sign up to set email alerts
|

Long term exposure to ambient air pollution and incidence of acute coronary events: prospective cohort study and meta-analysis in 11 European cohorts from the ESCAPE Project

Abstract: Objectives To study the effect of long term exposure to airborne pollutants on the incidence of acute coronary events in 11 cohorts participating in the European Study of Cohorts for Air Pollution Effects (ESCAPE).Design Prospective cohort studies and meta-analysis of the results.Setting Cohorts in Finland, Sweden, Denmark, Germany, and Italy.Participants 100 166 people were enrolled from 1997 to 2007 and followed for an average of 11.5 years. Participants were free from previous coronary events at baseline.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
315
3
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(351 citation statements)
references
References 43 publications
(78 reference statements)
18
315
3
15
Order By: Relevance
“…The adverse effects of air pollution on cardiovascular disease, lung cancer, and natural-cause mortality have been well established in several major epidemiological studies (5,6,7,8,9). The findings from the meta-analysis further add the evidence for the adverse effect of air pollution on risk of type 2 diabetes mellitus.…”
Section: European Journal Of Endocrinologymentioning
confidence: 68%
See 1 more Smart Citation
“…The adverse effects of air pollution on cardiovascular disease, lung cancer, and natural-cause mortality have been well established in several major epidemiological studies (5,6,7,8,9). The findings from the meta-analysis further add the evidence for the adverse effect of air pollution on risk of type 2 diabetes mellitus.…”
Section: European Journal Of Endocrinologymentioning
confidence: 68%
“…Though the increasing incidence of type 2 diabetes may be a result of increasing obesity, other potential risk factors have been proposed, such as air pollution (1,2,4). In recent years, several major epidemiological studies have showed that air pollution is obviously associated with increased risks of cardiovascular disease, lung cancer, and natural-cause mortality (5,6,7,8,9). However, the effect of air pollution on type 2 diabetes risk has not been clearly described.…”
Section: Introductionmentioning
confidence: 99%
“…Two Canadian papers found the opposite for both cardiovascular and COPD endpoints (Gan et al, 2010;Gan et al, 2013); in their joint models, BC dominated PM 2.5 . Several of the European papers reported significant associations with PM 2.5 , but not with PM abs in single-pollutant models Cesaroni et al, 2014;Fuks et al, 2014;MacIntyre et al, 2014;Pedersen et al, 2013;Raascshou-Nielsen et al, 2013); hence, within Europe the ESCAPE study appears to suggest that PM 2.5 mass is a better indicator of pollution of concern than PM abs . The Canadian studies suggest the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Normal mitochondrial function generates reactive oxygen species, and because of its proximal location, mtDNA is particularly vulnerable to oxidative damage. Effects of air pollution on mtDNA damage, including copy number variation,7 8‐hydroxy‐2′‐deoxyguanosine formation,8 and heteroplasmy,9 have been reported in human and animal studies. Recently, DNA methylation machinery was found in mitochondria,10 and mtDNA methylation levels have been shown to be associated with mitochondrial gene expression,11 which suggests possible roles for mtDNA methylation in controlling mitochondrial functions and biogenesis.…”
Section: Introductionmentioning
confidence: 99%